Monkeying around with venom: an increased resistance to α-neurotoxins supports an evolutionary arms race between Afro-Asian primates and sympatric cobras - Richard J. Harris (BMC, 2021)
Abstract Background Snakes and primates have a multi-layered coevolutionary history as predators, prey, and competitors with each other. Previous work has explored the Snake Detection Theory (SDT), which focuses on the role of snakes as predators of primates and argues that snakes have exerted a selection pressure for the origin of primates’ visual systems, a trait that sets primates apart from other mammals. However, primates also attack and kill snakes and so snakes must simultaneously avoid primates. This factor has been recently highlighted in regard to the movement of hominins into new geographic ranges potentially exerting a selection pressure leading to the evolution of spitting in cobras on three independent occasions. Results Here, we provide further evidence of coevolution between primates and snakes, whereby through frequent encounters and reciprocal antagonism with large, diurnally active neurotoxic elapid snakes, Afro-Asian primates have evolved an increased resistance to α-neurotoxins, which are toxins that target the nicotinic acetylcholine receptors. In contrast, such resistance is not found in Lemuriformes in Madagascar, where venomous snakes are absent, or in Platyrrhini in the Americas, where encounters with neurotoxic elapids are unlikely since they are relatively small, fossorial, and nocturnal. Within the Afro-Asian primates, the increased resistance toward the neurotoxins was significantly amplified in the last common ancestor of chimpanzees, gorillas, and humans (clade Homininae). Comparative testing of venoms from Afro-Asian and American elapid snakes revealed an increase in α-neurotoxin resistance across Afro-Asian primates, which was likely selected against cobra venoms. Through structure-activity studies using native and mutant mimotopes of the α-1 nAChR receptor orthosteric site (loop C), we identified the specific amino acids responsible for conferring this increased level of resistance in hominine primates to the α-neurotoxins in cobra venom. Conclusion We have discovered a pattern of primate susceptibility toward α-neurotoxins that supports the theory of a reciprocal coevolutionary arms-race between venomous snakes and primates.